Narasi Kesetiaan demi Keutuhan Rumah Tangga dalam Sastra Bali: Analisis “Geguritan Saci” - Karmini, Ni Nyoman (Jurnal Kajian Bali (Journal of Bali Studies), 2015)
Abstract Literary works usually convey social messages through the story and the reader should interpret the meaningbehind the symbols and metaphore in the story. This article analyzes a traditional Balinese literature of poetic genre,Geguritan Saci (The Song of Saci), which is rich in symbols and methaphore of Balinese local wisdom. By using the method of interpretation, this article discovered that there are at leastsix good character who symbolized in this story, namely, respect, responsible, good citizens, fair, caring, and trusthworthy. Based on these findings, this article suggests that the values contained in this poetic work should be read and disseminated to the society at large.
Keywords: geguritan poetic genre, Balinese literature, Geguritan Saci, love and loyalty